Análise econômica do mercado de carbono e dos efeitos de sua tributação - Amaral, Ian Rodrigues do (2010)
This work aims to make an economic analysis of the Carbon Market, as a new international commerce that, each day, atracts new parts or investors, either to assume voluntary or imposed greenhouse effect gas reducion marks, or to especulate with this market’s price variation and opportunity. Innitially there is a brief historic description of this market dawn, as well as the fundamental principles that leaded to its creation. The economic analysis itself begins with the suppliers and demandants exclusives characteristics, as well as the price formation in this market. The main objective of this research is, however, to study the negative effects, caused mainly by de excessive and not homogeneous taxing and positive effects that appears with the motivation that some internationals taxes offer to those who preffers the technological development other to the ordinary acquisition of international CREs.